A Video Projection Mapping Conceptual Design And Application: Yekpare - Ekim, Berna (The Turkish Online Journal Of Design Art And Communication, 2011)
Can recent developments in video projection techniques aid us in finding new ways of expressing our creativity and creative audio-visual works on a new surface other than the screen? Video Mapping is one of the newest video projection techniques that are used to turn almost any surface into a dynamic video display. The aim of video mapping is to create a physical illusion of images by combining audio-visual elements. Most of the mapping projects are used in fashion shows, corporate events, concerts and theatrical performances. Lately a new trend of video mapping system is being used on architectural and historical structures, buildings and displayed in public spaces to reach a wider audience. This paper will focus on 3 aspects of video mapping and its application; 1) the technical aspects of video mapping and its tools. 2) the conceptual development of the project YEKPARE and the application of video mapping on Haydarpasa Terminal within the Istanbul 2010 European Capital of Culture events. 3) the feedback from the audiences who have experienced the performance and the effects of video mapping.
Keywords: Ceeativity; Technology; Video Projection Mapping; Audio-visual; Conceptual Design; Yekpare